Experimental studies of the method of mutual load of induction motors - V. V. Kharlamov; D. I. Popov; P. S. Sokolov; L. E. Serkova (Омский научный вестник)
The article presents the results of comparison of experimental studies and mathematical modeling of the stand for testing induction motors by the method of mutual load. A detailed description of the composition of the experimental equipment, which is based on a pair of frequency converters and connected to them a pair of engines of the АИС71В4 type with a nominal power of 0,75 kW, the shafts of which are rigidly connected by a coupling. The mathematical model of the electromechanical system used in the calculations is presented, and its main assumptions are listed. A table of parameter values and graphs obtained from calculated and experimental data are presented. The analysis of the obtained data shows the possibility of using the considered mathematical model with the existing assumptions in the design of electrical complexes intended for testing induction motors by the method of mutual load.